Triglyceride concentrations in individual ova of New Zealand Snapper Chrysophrys auratus - Sabetian, Armagan; Cullen, Dannie; Huong Hoang, Luu; Lilkendey, Julian (Supplement to: Sabetian, A et al. (2020): Diversified bet-hedging explains the batch effect in New Zealand snapper Chrysophrys auratus. Aquaculture, 522, 735135, https://doi.org/10.1016/j.aquaculture.2020.735135, 2019)
Using an innovative analytical approach, we ascertained concentration and composition of triglycerides (TAGs) in individual ova of New Zealand snapper Chrysophrys auratus during three consecutive spawning events in one season. C. auratus broodstock were wild caught several months prior to the commencement of the study and kept in captivity at NIWA's (National Institute of Water and Atmospheric research) Bream Bay aquaculture facility, New Zealand. Thirty-six fish were split equally between two 20 m3 tanks, within the same recirculating system at a water exchange rate of 130 L min−1. Filtered (10 µm) seawater from Bream Bay was allowed to naturally increase to and then maintained at a temperature of 18°C to provide for optimum spawning temperature (Parsons et al., 2014 (doi:10.1080/00288330.2014.892013)). The photoperiod mirrored normal day light hours and fish were hand-fed to satiation daily using a diet of pilchard and squid. Eggs of C. auratus were collected on three separate dates: 21st December 2017, 11th January 2018 and 21st January 2018. Using a net, floating eggs were collected directly from the tanks after spawning and transferred into a large container with the same seawater, dried using a fine plastic mesh (150 μm), sorted and transferred into Eppendorf tubes and stored at -80°C in preparation for subsequent biochemical analysis using Liquid Chromatography-Mass Spectrometry [LC-MS]. Individual eggs were prepared and placed in glass low volume autosampler inserts. 40 μL of LC-MS grade isopropanol (Thermo Fisher NZ Ltd) containing 100 mg L-1 glyceryl tripentadecenoate [TG(15:1(10Z)/15:1(10Z)/15:1(10Z))] [TPD] as internal standard was added to the insert before the eggs were crushed. 10 μL of ultrapure water was then added to the sample and the glass insert was placed into a 1.5 ml Eppendorf tube and centrifuged at 6000 rcf for five minutes. Glass inserts were placed into 1.8 ml amber glass autosampler vials and capped for injection to LC-MS. In total, 147 eggs were prepared for TAG analysis. Triglyceride profiles were acquired using an Agilent 1200 Series liquid chromatograph with an Agilent 6420 triple quadrupole tandem mass spectrometer. An Agilent Poroshell 120 EC-C8 column measuring 150 × 2.1 mm with 2.7 μm packing material was used to separate TAGs and the injection volume was 25 μL. Three mobile phases were used: A) 89.9% ultrapure water and 10% acetonitrile [MeCN] with 0.1% acetic acid, B) MeCN with 0.1% acetic acid and 10mM NH4, and C) 80% IPA, 19.9% MeCN and 0.1% acetic acid with 10mM NH4. All mobile phase solvents and modifiers were mass spectrometry grade. The results were first visualised in TOPPView, an open-source software that is an integrated data visualisation and analysis tool for mass spectrometric data (Sturm and Kohlbacher, 2009 (doi:10.1021/pr900171m)). The m/z and retention times of each TAG peak was recorded and LIPID MAPS online tools for lipid research were used to assign carbon numbers to them, as described in Fahy et al. (2009; doi:10.1194/jlr.R800095-JLR200). TAG peaks were quantified relative to TPD using Agilent MassHunter Quantitative Data Analysis software. Quality was controlled using procedural and carryover blanks.
Keywords: Egg; fish; Sparidae; Triacylglycerol; Triglyceride